“Nani Palkhivala’s Green Paradigm: A Study of the Interconnectedness of Environmental Issues and Sustainable Development” - Sheeraz Naik; Mudasir Ahmad Sofi (Universitas Efarina, 2024)
This paper provides a critical analysis of Nani Palkhivala’s perspective on the Green Movement. Palkhivala, a renowned Indian jurist and environmentalist, was a vocal advocate for environmental conservation and sustainable growth. This paper examines Palkhivala’s views on the key issues facing the environment, the role of the Green Movement, and the importance of sustainable growth. The paper also discusses the implications of Palkhivala’s perspective for environmental policy and practice.